IDENTIFIKASI SERANGGA (INSEKTA) YANG MERUGIKAN PADA TANAMAN CABAI RAWIT DI DESA SISARAHILI EKHOLO KECAMATAN LOLOWAU KABUPATEN NIAS SEALATAN - Tonius Gulo; Darmawan Harefa (Jurnal Sapta Agrica, 2023)
Agriculture is an activity of utilizing biological resources by humans to produce food, industrial raw materials with the aim of fulfilling their needs. Chili (Capsicum annuum L.) is a horticultural commodity that has important economic value in Indonesia, so chili cultivation is very attractive to farmers. This study aims to determine the types of insects that are detrimental to chili plants. This type of research is descriptive qualitative research. This research was conducted from 16 December to 12 January 2023. This research was also carried out in the village of Sisarahili Ekholo, Lolowa'u District, Nias Selatan Regency. Identification is one of the ways or actions taken to find out the description of something being studied as a determinant or determination of identity, one example is insects (Insecta). Insects as a component of biodiversity have an important role in agricultural ecosystems, namely as herbivores, parasitoids, predators and environmental bioindicators. Based on the results of the research and discussion, it was found that the research obtained several types of insects, namely green grasshoppers (Atractomorpha), stinging bugs, stem and shoot borer insects (Scirpophaga innotata), green ladybugs (Hemiptera), and caterpillars. Suggestions from researchers are that people should be able to use appropriate techniques in exterminating insects on rice plants, because not all types of insects found on rice plants are harmful but some are beneficial such as: bees, butterflies and dragonflies and several other types of insects .